Determinants of Government Agency Accountability in Rokan Hilir - Putri, Annie Mustika; Rahayu, Norra Isnasia (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: This study aims to examine the influence of the implementation of Government Accounting Standards, Good Corporate Governance, supervision of financial reporting quality, and human resource competence on the performance accountability of government institutions. Methodology/approach: The research employed a quantitative approach using primary data collected through structured questionnaires distributed to finance officials and staff of Regional Apparatus Organizations in Rokan Hilir Regency. Respondents were selected based on their direct involvement in financial management, reporting, and accountability processes. Data were analyzed using multiple linear regression to test both partial and simultaneous effects of the independent variables on institutional accountability performance. Findings: The findings show that Government Accounting Standards, Good Corporate Governance, financial reporting supervision, and human resource competence positively and significantly affect government accountability performance. The instruments are valid and reliable, and the regression model meets classical assumption tests, indicating reliable results. Practical Implications: The research results indicate that government institutions should strengthen compliance with accounting standards, improve governance mechanisms, enhance oversight of financial reporting quality, and develop human resource competencies to achieve stronger accountability and improve the quality of public sector financial management and institutional governance. Originality: This study contributes to public sector accountability literature by examining the role of Government Accounting Standards, Good Corporate Governance, financial reporting supervision, and human resource competence in improving institutional accountability performance in Regional Apparatus Organizations of Rokan Hilir Regency.